2016
DOI: 10.1210/en.2016-1330
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Molecular and Endocrine Circadian Rhythms in Male Mice Lacking Bmal1 in the Adrenal Cortex

Abstract: The circadian rhythm of glucocorticoids affects diverse physiological systems, including stress responses and the coordination of rhythmic functions in peripheral and central tissues. Circadian clocks are considered to be important coordinators of glucocorticoid release and loss of the core clock component Brain and muscle Arnt-like protein-1 leads to ablation of behavioral and physiological rhythms, hypocortisolism, impaired ACTH, and behavioral stress responses. Transplantation and conditional clock gene kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Transplantation studies of adrenal tissues between clock‐deficient and ‐proficient mice strengthen this view, [ 44 ] but adrenocortical clock function itself seems dispensable for GC rhythmicity. [ 45 ] Overall, these findings imply that adrenal clocks are sufficient, but not necessary to create HPA axis rhythms. Moreover, PVN, pituitary and adrenal rather interpret systemic (SCN‐derived) signals in line with the above‐proposed gating model.…”
Section: Adrenocortical Clocks Gate Adrenocorticotropin Responses To mentioning
confidence: 94%
See 1 more Smart Citation
“…Transplantation studies of adrenal tissues between clock‐deficient and ‐proficient mice strengthen this view, [ 44 ] but adrenocortical clock function itself seems dispensable for GC rhythmicity. [ 45 ] Overall, these findings imply that adrenal clocks are sufficient, but not necessary to create HPA axis rhythms. Moreover, PVN, pituitary and adrenal rather interpret systemic (SCN‐derived) signals in line with the above‐proposed gating model.…”
Section: Adrenocortical Clocks Gate Adrenocorticotropin Responses To mentioning
confidence: 94%
“…[ 49 ] In contrast, mice with specific deletion of Bmal1 in the adrenal cortex using another CRE recombinase driver ( Cyp11a1 ) show no impairment in GC secretion under basal and stressed conditions. [ 45 ] Finally, a third paper using an aldosterone synthase‐controlled CRE driver to delete Bmal1 found complex alterations in daily GC rhythms and stress responses depending on light–dark conditions and gender of the mice. [ 50,51 ]…”
Section: Tissue Clock Knockouts Yield Various Phenotypesmentioning
confidence: 99%
“…GCs are mainly secreted via the adrenal cortex and display a strong circadian rhythm with a concentration peak at the beginning of the active as a direct result of an SCN‐adrenal clock interplay . However, adrenal specific Bmal1 deletion leads to dampened, yet persistent GC rhythms under constant conditions with no obvious metabolic alteration . By contrast, KO of Bmal1 in liver has severe consequences for the stability of blood glucose levels because mutant animals fail to export stored liver glucose into the bloodstream during fasting times .…”
Section: Peripheral Clocks In Energy Homeostasismentioning
confidence: 99%
“…5,102 However, adrenal specific Bmal1 deletion leads to dampened, yet persistent GC rhythms under constant conditions with no obvious metabolic alteration. 103 By contrast, KO of Bmal1 in liver has severe consequences for the stability of blood glucose levels because mutant animals fail to export stored liver glucose into the bloodstream during fasting times. 68 Vice versa, the rescue of liver clock function in Clock mutant mice improves glucose tolerance and body weight development under HFD with restored food intake rhythms and energy expenditure.…”
Section: Me Taboli C Reg Ul Ati On In Circ Ad Ian Clo Ck Mutant Mi Cementioning
confidence: 99%
“…Abrogation of Bmal1 function in Mc2r-expressing adrenal cells abolishes circadian corticosterone rhythms (Son et al 2008). However, a recent study using a different strategy to eliminate Bmal1 in adrenocortical cells found no significant change in glucocorticoid release under basal or stressed conditions (Dumbell et al 2016). Thus, the balance of work conducted so far indicates that the molecular clock regulates adrenal function, but understanding the nature and location of stress-circadian interactions requires further study.…”
Section: Stress Alters the Adrenal Clockmentioning
confidence: 99%